Association of Statewide Certificate of Need Regulations With Percutaneous Coronary Intervention Appropriateness and Outcomes. Issue 2 (22nd January 2019) - Chui, Philip W.; Parzynski, Craig S.; Ross, Joseph S.; Desai, Nihar R.; Gurm, Hitinder S.; Spertus, John A.; Seto, Arnold H.; Ho, Vivian; Curtis, Jeptha P.
Abstract : Background: Certificate of need (CON) regulations are intended to coordinate new healthcare services, limit expansion of unnecessary new infrastructure, and limit healthcare costs. However, there is limited information about the association of CON regulations with the appropriateness and outcomes of percutaneous coronary interventions (PCI). The study sought to characterize the association between state CON regulations and PCI appropriateness. Methods and Results: We used data from the American College of Cardiology's CathPCI Registry to analyze 1 268 554 PCIs performed at 1297 hospitals between January 2010 and December 2011. We used the Appropriate Use Criteria to classify PCI procedures as appropriate, maybe appropriate, or rarely appropriate and used Chi‐square analyses to assess whether the proportions of PCIs in each Appropriate Use Criteria category varied depending on whether the procedure had been performed in a state with or without CON regulations. Analyses were repeated stratified by whether or not the procedure had been performed in the setting of an acute coronary syndrome (ACS). Among 1 268 554 PCI procedures, 674 384 (53.2%) were performed within 26 CON states. The proportion of PCIs classified as rarely appropriate in CON states was slightly lower compared with non‐CON states (3.7% versus 4.0%, P <0.01). Absolute differences were larger among non‐ACS PCI (23.1% versus 25.0% [ P <0.01]) and were not statistically significantly different in ACS (0.62% versus 0.63% [ P >0.05]). Conclusions: States with CON had lower proportions of rarely appropriate PCIs, but the absolute differences were small. These findings suggest that CON regulations alone may not limit rarely appropriate PCI among patients with and without ACS. Abstract : See Editorial by Anderson